Force in the Construction of the Theoretical Framework in Scientific Papers: A Systemic-Functional Linguistics Approach - Barletta, Norma Patricia; Chamorro, Diana; Mizuno, Jorge (Íkala, Revista de Lenguaje y Cultura, 2020)
Opposite to what is traditionally stated, the theoretical framework often constitutes an independent section in research articles. Therein writers establish the theoretical tradition that supports their research and make an account of the theoretical and research developments in their discipline, specifically, in their topic of research, thus establishing a dialogue with other voices. This article examines how writers organize their theoretical framework by means of verbal clauses using the resources of the graduation subsystem proposed by the systemic functional linguistics to express force —which will help them to construct their authorial voice. This study analyzed the verbal clauses and the graduation resources of the theoretical frameworks in 20 research articles in Spanish language published in Colombian journals from the area of applied linguistics. Findings show the variety of resources deployed by writers in their verbal clauses to strengthen their commitment to their tenets, especially in prominent places of their theoretical framework, such as the macroTheme, hyperThemes, macroNew and hyperNew. Awareness of these theoretical framework features may be relevant for teaching academic writing.